LEVEL : an exhibition of work from past guest artists of Haagweg 4. - Keisjer, Hester; Centrum Beeldende Kunst, Leiden (Derby : University of Derby, 2000)
Bakker, Emily ; Clark, Donald ; Currie, Alasdair ; Dignan, Paul ; Fahrenholz, Mateusz ; France, John ; Jordan, Melanie ; Troth, Miriam
Level, Centrum Beeldende Kunst, Leiden, 30 January until 5 March 2000
kunstcatalogus